Controlling Culex Quinquefasciatus Say, 1823 (Diptera: Culicidae) Using Several Lysinibacillus Sphaericus Isolates Endogenic to Indonesia - Ika Indayati; Hari Purwanto (Jurnal Biologi Tropis, 2021)
Mosquito-borne diseases include tropical diseases such as malaria, filariasis, dengue fever, chikungunya, yellow fever and cerebral fever are still major health problems in Indonesia and on a global scale. Various methods have been used to overcome this, including controlling vector mosquitoes using the entomopathogenic microbial Lysinibacillus sphaericus. This study aims to identify bacterial isolates collected based on the 16S rRNA gene and to carry out the pathogenicity test of the bacterial isolates collected on Cx. quinquefasciatus larvae. Bacterial isolates used in this study were collected from root soil, bird droppings and guano. The identification of the type of bacteria was carried out based on the 16S rRNA gene fragment. Based on the results of the 16S RNA sequence analysis of isolates 229C, 6B4, 6.2 and 4D21, it was found that the four isolates were included in the L. sphaericus species with similarity scores ranging from 97% to 100%. The pathogenicity of bacteria was measured based on the mortality of Cx. quinquefasciatus larvae to know whether it has pathogenicity equal to or higher than strain 1593. The pathogenicity test results of 6 isolates 15.4, 229C, 1593, 6B4, 6.2 and 4D21 showed that isolate 15.4 has the highest larval mortality rate, so it is potentially used as a biological agent to control disease vector mosquitoes.